Dangers and Benefits of Social Media on E-Professionalism of Health Care Professionals: Scoping Review - Tea Vukušić Rukavina; Joško Viskić; Lovela Machala Poplašen; Danko Relić; Marko Marelić; Drazen Jokic; Kristijan Sedak (JMIR Publications, 2021)
BackgroundAs we are witnessing the evolution of social media (SM) use worldwide among the general population, the popularity of SM has also been embraced by health care professionals (HCPs). In the context of SM evolution and exponential growth of users, this scoping review summarizes recent findings of the e-professionalism of HCPs. ObjectiveThe purpose of this scoping review is to characterize the recent original peer-reviewed research studies published between November 1, 2014, to December 31, 2020, on e-professionalism of HCPs; to assess the quality of the methodologies and approaches used; to explore the impact of SM on e-professionalism of HCPs; to recognize the benefits and dangers of SM; and to provide insights to guide future research in this area. MethodsA search of the literature published from November 1, 2014, to December 31, 2020, was performed in January 2021 using 3 databases (PubMed, CINAHL, and Scopus). The searches were conducted using the following defined search terms: "professionalism" AND "social media" OR "social networks" OR "Internet" OR "Facebook" OR "Twitter" OR "Instagram" OR "TikTok." The search strategy was limited to studies published in English. This scoping review follows the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) guidelines. ResultsOf the 1632 retrieved papers, a total of 88 studies were finally included in this review. Overall, the quality of the studies was satisfactory. Participants in the reviewed studies were from diverse health care professions. Medical health professionals were involved in about three-quarters of the studies. Three key benefits of SM on e-professionalism of HCPs were identified: (1) professional networking and collaboration, (2) professional education and training, and (3) patient education and health promotion. For the selected studies, there were five recognized dangers of SM on e-professionalism of HCPs: (1) loosening accountability, (2) compromising confidentiality, (3) blurred professional boundaries, (4) depiction of unprofessional behavior, and (5) legal issues and disciplinary consequences. This scoping review also recognizes recommendations for changes in educational curricula regarding e-professionalism as opportunities for improvement and barriers that influence HCPs use of SM in the context of e-professionalism. ConclusionsFindings in the reviewed studies indicate the existence of both benefits and dangers of SM on e-professionalism of HCPs. Even though there are some barriers recognized, this review has highlighted existing recommendations for including e-professionalism in the educational curricula of HCPs. Based on all evidence provided, this review provided new insights and guides for future research on this area. There is a clear need for robust research to investigate new emerging SM platforms, the efficiency of guidelines and educational interventions, and the specifics of each profession regarding their SM potential and use.